2022
DOI: 10.1021/acsenergylett.2c01841
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Co/O Redox Chemistry via Fermi Level Regulation for Stable High-Voltage LiCoO2

Abstract: LiCoO2 (LCO) is ideal for 3C electronics due to its high tap density. However, the excessive O → Co charge transfer at high delithiation leads to irreversible Co reduction, O release, and structural degradation, deteriorating the high-voltage performance of LCO. Herein, we propose to regulate the intrinsic Fermi level via uneven trace Zr/Mg doping. First, the increase of electron density in the Fermi level mitigates both the O oxidation/coupled Co reduction through alleviating the O → Co charge transfer, restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The activated oxygen redox (O 2− ↔O − ) tends to be induced in excess at some specific domains, leading to an irreversible structural degradation and electrochemical performance decay. [ 45 ] Moreover, the surface O − with a higher ionic mobility than O 2− can easily escape from LCO particles. [ 46 ] The O 2 release further promotes the local structure damage and form corrosion cavities at surfaces.…”
Section: Degradation Mechanisms and Direct Recycling Strategies Of Li...mentioning
confidence: 99%
“…The activated oxygen redox (O 2− ↔O − ) tends to be induced in excess at some specific domains, leading to an irreversible structural degradation and electrochemical performance decay. [ 45 ] Moreover, the surface O − with a higher ionic mobility than O 2− can easily escape from LCO particles. [ 46 ] The O 2 release further promotes the local structure damage and form corrosion cavities at surfaces.…”
Section: Degradation Mechanisms and Direct Recycling Strategies Of Li...mentioning
confidence: 99%
“…[ 5 ] Numerous strategies, including constructing surface protective layer for the elimination of Co dissolution, tuning Co/O electronic band structure for the reduction of lattice oxygen loss and multiple elements doping for the suppression of phase transitions, have been demonstrated effective in stabilizing the high‐delithiated‐state structure of LCO. [ 6 ] However, till now, rare studies report a long lifespan LCO (e.g., exceed 600 cycles) with a good capacity retention (e.g., >80%), which means that there are still fundamental structure‐stability problems need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Essentially, these issues initially stem from near-surface lattice oxygen (O 2À ) instability and derived Co 4+ due to de-lithiation to high voltages of especially 44.5 V. More precisely, the near-surface lattice becomes highly lithium-deficient compared to the bulk lattice during deep de-lithiation causing oxygen redox (O 2À -O nÀ , n o 2) to participate in charge compensation, which can also contribute to considerable additional capacity. 3,[10][11][12][13] However, this process synchronously becomes highly irreversible as charging approaches 4.6 V. As a result, O 2À is highly susceptible to over-oxidation by Co 4+ to peroxide ions (O À ) with high mobility and activity, which will further evolve into O 2 , leading to oxygen loss. 3,5,10,11,14,15 It is reported that the large number of oxygen vacancies caused by oxygen loss triggers the collapse of the crystal structure from the surface to the bulk.…”
Section: Introductionmentioning
confidence: 99%